Pseudomonads Rule Degradation of Polyaromatic Hydrocarbons in Aerated Sediment - Wald, Jiri; Hroudova, Miluse; Jansa, Jan; Vrchotova, Blanka; Macek, Tomas; Uhlik, Ondrej (Frontiers in Microbiology, 2015)
Given that the degradation of aromatic pollutants in anaerobic environments such as sediment is generally very slow, aeration could be an efficient bioremediation option. Using stable isotope probing (SIP) coupled with pyrosequencing analysis of 16S rRNA genes, we identified naphthalene-utilizing populations in aerated polyaromatic hydrocarbon (PAH)-polluted sediment. The results showed that naphthalene was metabolized at both 10°C and 20°C following oxygen delivery, with increased degradation at 20°C as compared to 10°C – a temperature more similar to that found in situ. Naphthalene-derived 13C was primarily assimilated by pseudomonads. Additionally, Stenotrophomonas, Acidovorax, Comamonas and other minor taxa were determined to incorporate 13C throughout the measured time course. The majority of SIP-detected bacteria were also isolated in pure cultures, which facilitated more reliable identification of naphthalene-utilizing populations as well as proper differentiation between primary consumers and cross-feeders. The pseudomonads acquiring the majority of carbon were identified as Pseudomonas veronii and P. gessardii. Stenotrophomonads and Acidovorax defluvii, however, were identified as cross-feeders unable to directly utilize naphthalene as a growth substrate. PAH degradation assays with the isolated bacteria revealed that all pseudomonads as well as Comamonas testosteroni degraded acenaphthene, fluorene and phenanthrene in addition to naphthalene. Furthermore, P. veronii and C. testosteroni were capable of transforming anthracene, fluoranthene and pyrene. Screening of isolates for naphthalene dioxygenase genes using a set of in-house designed primers for Gram-negative bacteria revealed the presence of such genes in pseudomonads and Comamonas testosteroni. Overall, our results indicated an apparent dominance of pseudomonads in the sequestration of carbon from naphthalene and potential degradation of other PAHs upon aeration of the sediment at both 20°C and 10°C.